2014
DOI: 10.1037/tep0000039
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Critical Events in Supervision Model using gender related events.

Abstract: The purpose of this study was to evaluate the applicability of the Critical Events Model to the psychotherapy supervisory process, with a focus on gender related events (GREs) experienced by counseling trainees. Four research questions framed the study: (1) What types of GREs do trainees experience in psychotherapy supervision? (2) How do supervisors attend to these GREs? (3) What is the relationship between the interventions that supervisors use and the resolution of the critical event? Finally, given the imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 26 publications
1
29
0
Order By: Relevance
“…The fairly high proportion of gender discussions in this study suggests that it continues to remain one of the most addressed topics for supervisees. Given the recent findings regarding the continued gender-related critical events in supervision (Bertsch et al, 2014) such attention seems warranted. Moreover, our findings revealed that there seemed to be an interest in talking about issues related to ethnicity and religion/spirituality.…”
Section: Content Of Cultural Topics Discussedmentioning
confidence: 96%
“…The fairly high proportion of gender discussions in this study suggests that it continues to remain one of the most addressed topics for supervisees. Given the recent findings regarding the continued gender-related critical events in supervision (Bertsch et al, 2014) such attention seems warranted. Moreover, our findings revealed that there seemed to be an interest in talking about issues related to ethnicity and religion/spirituality.…”
Section: Content Of Cultural Topics Discussedmentioning
confidence: 96%
“…There has, however, been little research on this model. What is known, in general, is that negative events in supervision tend to have a profound influence on supervisees' feelings (e.g., Nelson & Friedlander, 2001); moreover, negative events detract from the supervisory alliance (e.g., Bertsch et al, 2014;Ramos-Sánchez et al, 2002) and inhibit trainees' inclination to disclose relevant material to their supervisors (Walker, Ladany, & Pate-Carolan, 2007). What is not known is how effective supervisors behave so as to create an interpersonal environment that is most conducive to supervisees' professional growth and development.…”
mentioning
confidence: 99%
“…The effects of appropriately discussing cultural issues in supervision have been reported to enrich the supervisory relationship, increase satisfaction with supervision and heighten supervisee awareness to cultural considerations in therapy (Burkard et al, 2006;Gatmon et al, 2001). In contrast, the lack of culturally sensitive supervision can negatively impact upon the supervisory relationship (Bertsch et al, 2014;Walker, Ladany, & Pate-Carolan, 2007) and on supervisee's emotional safety, confidence and well-being (Constantine & Sue, 2007;Wong et al, 2013). It may also diminish supervisee disclosure and negatively impact on therapy (Burkard et al, 2006;Walker et al, 2007).…”
Section: Cultural and Multicultural Considerationsmentioning
confidence: 91%